2021
DOI: 10.1080/07481187.2021.1888826
|View full text |Cite
|
Sign up to set email alerts
|

Mortality salience in an offline and online setting

Abstract: The current study aims to examine the effects of mortality salience effects on worldview defense in an offline and online setting. Participants were 146 (66 offline and 80 online) Singaporeans. Participants were randomly assigned to either the mortality salience condition or the control condition and after a delay completed a Worldview Defense Assessment. No significant mortality salience effects on worldview defense occurred in either setting. The results might be explained by the Asian sample, Singapore's cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…In TMT research, the results of online samples have been mixed. Some online TMT research has resulted in atypical results [ 91 ] and failures to replicate [ 32 , 47 ]. Yet there are numerous other published studies that have been successful in inducing MS using essay primes via online or MTurk administration [ 93 95 ].…”
Section: Study 6: Summing Up Studies 1–5 Via Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In TMT research, the results of online samples have been mixed. Some online TMT research has resulted in atypical results [ 91 ] and failures to replicate [ 32 , 47 ]. Yet there are numerous other published studies that have been successful in inducing MS using essay primes via online or MTurk administration [ 93 95 ].…”
Section: Study 6: Summing Up Studies 1–5 Via Meta-analysismentioning
confidence: 99%
“…Some argue it is a culturally-laden, if not culture-bound, phenomenon [e.g., 35 , 37 ], others have challenged TMT’s definition of self-esteem [ 39 , 40 ], its interpretation of evolutionary principles [e.g., 41 43 ], its rationale for using a delay between MS and the outcome of interest [ 21 , 24 ], its postulation that MS itself is unique in generating effects [ 44 46 ], and the proposed mechanisms for why MS leads to its effects [ 22 ]. There have also long been failures to replicate some of the basic effects seen in TMT literature [e.g., Ochsman, personal communication, cited in 27 ], even with meticulous methods, faithful experimental conditions, and enviable sample sizes [ 31 , 32 , 47 50 ]. Although meta-analyses indicate a fairly robust effect of TMT on a host of dependent variables [ 19 ], Schindler and colleagues [ 30 ] found that the prototypical dependent variable—worldview defense—is not robustly found across studies when accounting for publication bias, control conditions, researcher effects (namely, researcher degrees of freedom), and other key components [ 30 ].…”
Section: Introductionmentioning
confidence: 99%